Modeling the rate of descent of bulk material from rotating conical disk under conditions of excess pressure (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The paper presents a mathematical model of the movement of an elementary particle of bulk material on a conical disk rotating at a constant angular velocity. The effect of overpressure in the dosing zone on the trajectory and dynamics of particle motion is investigated. The modeling takes into account gravity, friction, centrifugal and Coriolis forces, as well as the vertical component of the pressure force. Numerical modeling was carried out, the results of which allow us to substantiate the design and operating parameters of a multicomponent dosing and mixing device to ensure uniform supply of components. The results can be used to design efficient systems for mixing bulk materials in the chemical, food, and construction industries.
Keywords: modeling; batcher-mixer; conical disk; excess pressure; research; dosing; Runge-Kutta method; speed